2017
DOI: 10.1038/s41598-017-16657-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance on emotional tasks engaging cognitive control depends on emotional intelligence abilities: an ERP study

Abstract: Cognitive control is a key process in decision making and adequately adapting our behavior to the environment. Previous studies have provided evidence of a lower capacity for cognitive control in emotion-laden contexts in comparison with neutral contexts. The aim of the present research was to study changes in cognitive control performance as a function of emotional intelligence (EI) level in contexts involving emotional information. The study sample was composed of 2 groups of 22 participants each: the high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 58 publications
(61 reference statements)
3
29
1
2
Order By: Relevance
“…The results show that negative mood and anticipated fear are two factors of the relationship between trait EI and risk-taking in decision-making processes among adults [ 158 ]. Research has also shown this positive correlation between emotional intelligence and cognitive processes and this demonstrates the important role that emotional intelligence plays with emotion and cognition, thus, empowering individuals and their personality and benefitting the whole society [ 159 , 160 , 161 , 162 , 163 , 164 ].…”
Section: Discussionmentioning
confidence: 96%
“…The results show that negative mood and anticipated fear are two factors of the relationship between trait EI and risk-taking in decision-making processes among adults [ 158 ]. Research has also shown this positive correlation between emotional intelligence and cognitive processes and this demonstrates the important role that emotional intelligence plays with emotion and cognition, thus, empowering individuals and their personality and benefitting the whole society [ 159 , 160 , 161 , 162 , 163 , 164 ].…”
Section: Discussionmentioning
confidence: 96%
“…In Go-situation we chose time windows corresponding to the time of P3 peak and the following slow positive waveform, the LPP, which is reported to be larger when emotional stimuli is only attended to but reduced with successful reappraisal of emotion (Hajcak and Nieuwenhuis, 2006 ), i.e., 700–800 ms and 800–900 ms in our paradigm. In NoGo-situation we chose time windows around the N2 peak and the P3 peak, i.e., 600–700 ms and 700–800 ms, for further analysis as these potentials are thought to reflect different phases of cognitive control required for response inhibition and are known to be modulated by emotion with the extent of modulation reflecting factors influencing emotion-cognition interaction such as emotional intelligence (Megías et al, 2017 ). The amount of selected time windows was kept to minimum to control for familywise error rate.…”
Section: Methodsmentioning
confidence: 99%
“…Such simple threat-related stimuli used in the current study are known to be prioritized for attention networks (Vuilleumier and Schwartz, 2001 ) and provide means to tap into potential alterations in emotion-attention interaction due to OFC lesion. Because the N2 potential reflects early cognitive control, particularly in a response inhibition/NoGo task (Donkers and van Boxtel, 2004 ; Megías et al, 2017 ), and the P3 potential reflects response inhibition and possibly response cancellation in a NoGo task (Kok et al, 2004 ; Randall and Smith, 2011 ; Groom and Cragg, 2015 ) as well as attention allocation (Polich, 2007 ), they are suitable candidates for studying the interaction of emotion and attention/cognitive control. We further combined these amplitudes to N2P3 peak-to-peak amplitude as our previous studies with clinical populations have suggested that in contrast to single peak measurements, N2P3 peak-to-peak amplitude may provide a more robust measure of attention (Mäki-Marttunen et al, 2015 , 2017 ) and help control for abnormal EEG shifts and slow waves frequently observed in clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…In one version, the emotional stimulus was a task-irrelevant distractor: Go versus Nogo responses were signaled by probe stimuli independent from the emotional content. In the other version, the emotional stimulus was the task-relevant probe stimulus: participants had to perform Go versus Nogo responses based on the emotional content of the stimuli (Megías, Gutiérrez-Cobo, Gómez-Leal, Cabello, & Fernández-Berrocal, 2017). This allowed us to test whether task-relevant emotional, in this case threatening, stimuli would be more able to induce the theoretically expected threat-enhanced impulsivity: more commission errors and lower Go-…”
Section: Introductionmentioning
confidence: 99%